2013
DOI: 10.1186/1471-2458-13-5
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of a complex intervention by primary care nurses to increase walking in patients aged 60–74 years: protocol of the PACE-Lift (Pedometer Accelerometer Consultation Evaluation - Lift) trial

Abstract: BackgroundPhysical activity is essential for older peoples’ physical and mental health and for maintaining independence. Guidelines recommend at least 150 minutes weekly, of at least moderate intensity physical activity, with activity on most days. Older people’s most common physical activity is walking, light intensity if strolling, moderate if brisker. Less than 20% of United Kingdom 65–74 year olds report achieving the guidelines, despite most being able to. Effective behaviour change techniques include str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 51 publications
(60 reference statements)
1
39
0
Order By: Relevance
“…The trial protocol has been published ( S1 Text ) [ 13 ]. A two-arm parallel cluster randomised trial, randomised by household, compared a complex intervention to increase walking carried out over a 3 month period with a usual care control group.…”
Section: Methodsmentioning
confidence: 99%
“…The trial protocol has been published ( S1 Text ) [ 13 ]. A two-arm parallel cluster randomised trial, randomised by household, compared a complex intervention to increase walking carried out over a 3 month period with a usual care control group.…”
Section: Methodsmentioning
confidence: 99%
“…Those selected for telephone interview were reminded of their initial consent to be interviewed and if they were happy to go ahead, their consent was also sought to be audio-recorded. The interview schedule was modelled on that used during a preceding PA trial [ 30 ] and refined by discussion between authors and piloting prior to recruitment. The schedule was adapted slightly after the first 15 interviews, following discussion between co-authors, to ensure better understanding of the questions and also to probe participants’ memories further with regard to meeting with the practice nurse, as we found that few participants were spontaneously volunteering specific details.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, our data correspond to a recently published study protocol for a walking intervention [39]. The authors plan to conduct the same recruitment steps as we did in our study, with the exception that they cooperate with three much larger (list size of at least 10,000 patients) GP practices.…”
Section: Discussionmentioning
confidence: 75%